2020
DOI: 10.1177/0890117120934610
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Nutrition Assistance Program (SNAP)-Authorized Grocery, Convenience, Dollar, and Restaurant or Delivery Service Settings Are Associated With Increased Obesity Prevalence in Virginia

Abstract: Purpose: United States Department of Agriculture Supplemental Nutrition Assistance Program (SNAP) participants use SNAP-authorized stores for dietary purchases. Relationships between obesity prevalence and access to grocery and varied nontraditional (eg, dollar, drug, and convenience) SNAP settings are underexplored. This research aimed to determine the association of a full range of SNAP-authorized stores with obesity prevalence in Virginia. Design: The SNAP Retailer Locator was used to cross-sectionally iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In our study population, low access to grocery stores was associated with a decreased likelihood of being obese. This finding is consistent with other research that has found a positive association between greater grocery store access and increased obesity rates (39) . When this relationship was examined in the two subpopulations, we found it to be significant only among AI/AN who lived in counties with higher poverty.…”
Section: Discussionsupporting
confidence: 93%
“…In our study population, low access to grocery stores was associated with a decreased likelihood of being obese. This finding is consistent with other research that has found a positive association between greater grocery store access and increased obesity rates (39) . When this relationship was examined in the two subpopulations, we found it to be significant only among AI/AN who lived in counties with higher poverty.…”
Section: Discussionsupporting
confidence: 93%
“…This likely led to lower BIA-Obesity scores being recorded among all retailers. Last, analysis regarding traditional versus nontraditional formats could be more nuanced [ 94 ]. However, certain nontraditional formats were not frequently observed in this research (e.g., only one prominent SNAP-authorized retailer was classified as a club format), which limited opportunities to understand variations among several nontraditional formats.…”
Section: Discussionmentioning
confidence: 99%
“…Our review results also suggest supermarkets may prime consumers more than smaller stores regarding the purchase of SSB products, although this may be related to store size (e.g., more space for numerous SSB displays and marketing strategies). This may be one reason supermarkets have been associated with the prevalence of obesity, 91 despite their historical use as an indicator of favorable community food access. Research has shown optimal food access more complex than supermarket distance, [92][93][94] and application of environmental tools and/or scanner purchasing data 95 to understand the influence of SSB MMCA strategies on consumers' purchase of healthy and less healthy beverages is warranted among varied store formats and communities.…”
Section: Profile Pricing and Promotion Strategies To Sell Ssb Productsmentioning
confidence: 99%